На огороде и близ него: стихи на удм. яз. / К. Герд - Герд Кузебай (Удмуртия, 2011)
Экземпляры: б/ф-5 (20150202) / Инвентарный номер: 34905 / Цена: 61.81 / Авт.знак: Г 37 / ГРНТИ: 17 / ББК: 84 (2Рос=Удм)